(untitled) (Grande Medical Journal, 2021)
Background: The Novel Coronavirus disease (COVID-19) rapidly evolved as a pandemic in late 2019 AD. Many hospitals had to reduce cancer diagnosis and treatment for various reasons such as, re-allocation of resources, work force for COVID-19 care and to reduce infection to health care workers. Our unit made a policy to continue cancer surgery. The aim of the present study is to report peri-operative variables, outcome and adaptation we made to continue the surgical services. Materials and methods: All consecutive patients who underwent surgery in a single unit of a cancer hospital from March 2020 to February 2021 were included in the study. Data was extracted from the prospectively maintained database of our unit. Results: One hundred and seventy-eight surgeries for cancer were performed over the study period. The median age of patients was 53.5 years (IQR: 43-65years), 22 patients were more than 70 years of age. Majority of patients were American Society of Anaesthesiologist (ASA) status I (69.66%). The most common pathology was gastrointestinal (43%) followed by breast cancer (29%). Except initial 12 patients, rest 166 patients underwent pre-operative screening with RT-PCR test for COVID-19. None of the patients developed symptoms of COVID-19 in post-operative period. There were 30 Clavein-Dindo grade I/II, 1 grade IIIb and 2 grade V complications. There was no unusual post operative course or delay in discharge due COVID-19 disease. Conclusions: By following previously known standardised protocols and adapting the new ones for COVID-19, surgical services for cancer can be conducted safely during pandemic.